Genesis and organic matter chemistry of sombric horizons in subtropical soils (Paraná State, Brazil) - Chiapini, Mariane (2017)
Soil organic matter (SOM) plays an important role in the global carbon cycle. Therefore, it is important to understand the stability of SOM, which is related to several processes. Its intrinsic properties may be related to its stability, for example black carbon is considered to be relatively resistant to degradation. In most soils, the dark horizons coincide with the superficial layers or horizons due to the greater accumulation of organic matter, but in the southern states of Brazil, the presence of soils with dark subsurface horizons is frequently observed. The dark subsurface horizon of these soils are similar to a sombric horizon. Aspects about its origin, formation and preservation have not yet been fully elucidated. The objective of this work is to understand the formation of \'sombric\' horizons in soils of the region from Tijucas do Sul (Paraná, Brazil). Five soil profiles were described and collected, from which three originate from a toposequence and contained a \'sombric\' horizon (P1-P3), a reference soil that is representative of the area (P5) and an intermediate soil (P4) that showed morphology between the reference soil and the soils with a \'sombric\' horizon. To this end SOM is studied for its molecular composition by the pyrolysis technique coupled to gas chromatography and mass spectrometry (pyrolysis-GC-MS). In addition, 13C isotopic composition (δ13C) and phytolytic composition were studied in order to understand paleoclimatic conditions. These results will be related to past environmental conditions using 14C dating techniques, and supported by classical soil analysis. The samples of the horizons were submitted to the SOM chemical fractionation, generating two fractions: extractable fraction with NaOH (EXT) and residue (RES). The morphology of the profiles showed an intense biological activity in A horizons and a wide distribution of microfragments of charcoals. The lateral continuity of \'sombric\' horizons in toposequence soils was also observed, which differentiated them (P1-P3) from buried A horizons. The distribution of SOM in the fractions studied was the same for the five profiles studied: EXT> RES. Products related to wildfires such as polyaromatics (PAHs; BC) were found in all profiles, but in greater relative abundance in the \'sombric\' horizons, indicating a higher incidence of fire during the formation of these horizons and these compounds can be related to the maintenance of dark color of the \'sombric\' horizons. In relation to the paleoclimatic conditions it was observed that the dark subsurface horizons were developed during the Mid-Holocene under vegetation composed mainly by C4 grasses with shrubs, evidencing a drier climate corresponding to a higher fire incidence.